Students' Response to The Use of Tracker Software in Physics Laboratory - Karuru, Perdy; Silka, Silka; Gela M, Bergita; Pakiding, Alexander; Lolang, Enos (Devotion : Journal of Research and Community Service, 2023)
This research aims to evaluate how physics education students respond to the use of tracker software in the implementation of physics laboratory experiments covering projectile motion. The study was conducted in the physics laboratory at the Universitas Kristen Indonesia Toraja (UKI Toraja) and involved 10 (ten) physics education students. Research data were obtained through questionnaires and analyzed quantitatively by calculating percentages. The utilization of tracker software in the implementation of projectile motion experiments enables students to easily observe and analyze the phenomenon of projectile motion. Students feel that experiments on projectile motion using tracker software are relatively straightforward to understand and learn. The results of student responses to the implementation of physics laboratory experiments involving tracker software in projectile motion show an approval rate of 64.4%. Therefore, it can be concluded that students exhibit a positive response and agree with the use of tracker software in physics laboratory experiments.